The elimination of the yield point phenomenon in a new zirconium alloy: Influence of degree of recrystallization on the tensile properties. (August 2019) - Shi, Huigang; Li, Jiuxiao; Mao, Jianwei; Lu, Weijie
Abstract: The different yielding behaviors of annealed samples of Zr-Sn-Nb-Fe-Cu alloy and its dependence on microstructure have been studied. The yield drop was observed in samples with complete recrystallization, and this behavior gradually disappeared with the reduction of recrystallization degree. Meanwhile, as the strain rate increased, the yield point phenomenon (YPP) became less prominent in the stress-strain curves. It was assumed that solute-dislocation interaction mechanism and dislocation multiplication mechanism were responsible for this phenomenon. The unload-reload tests proved that the evolution of yielding behavior was caused by the increase of mobile dislocations with increasing pre-strain. Graphical abstract: Unlabelled Image